Producer practices and attitudes: Non-replacement male calf management in the Australian dairy industry - Vicic, Veronika; Saliba, Anthony J.; Campbell, Michael A.; Xie, Gang; Quinn, Jane C. (Frontiers in Veterinary Science, 2022)
Despite growing consumer expectations, there is currently no production standard for non-replacement male dairy calves that maximizes their economic viability. Producers have highlighted the need to match consumer expectations, but even with broadscale welfare improvement across the dairy industry challenges remain at providing reliable and valuable pathways for non-replacement male dairy calves for beef production. A key consumer concern has been the use of on-farm euthanasia. Euthanasia has been a catalyst for change in the industry from a human and animal welfare perspective. There has been evidence to show the practice of euthanasia can lead to decline in personnel wellbeing. To investigate the relationship between on-farm management practices of non-replacement male dairy calves, and producer perceptions of their value proposition, an online questionnaire was provided to Australian dairy producers between June and October 2021. The aim was to identify supply-chain profitability of non-replacement male calves and investigate the attitudes and effects of euthanasia as part of managing these calves. A total of 127 useable responses were obtained and Bayesian Network (BN) was utilized to model the interdependencies between management practices and wellbeing among participants. Results indicated that, in general, dairy producers desired and utilized high welfare standards and good management practices in their enterprises with regard to non-replacement male calves as well as expressing the desire to meet industry and consumers expectations. In line with anecdotal reports of a reduction in practice, euthanasia was not identified as a common practice in this group, however producers were still accessing early life markets for non-replacement male calves with operational requirements and environmental factors influencing their decisions. Producers expressed dissatisfaction with market access for their calves, as well as the lack of suitability of Australian beef grading standards for dairy bred carcasses. Australian dairy managers and owners identified that euthanasia influenced employee wellbeing, however, they did not acknowledge euthanasia had an effect on their own wellbeing. Overall, the findings of this study indicate that all non-replacement male calf breeds had the potential to access profitable markets and avoidance of euthanasia is a strong driver of change among dairy beef production systems in Australia.